Deep Learning Approaches for Aspect-Based Sentiment Analysis in Customer Reviews (International Journal of Food and Nutritional Sciences, 2019)
This paper introduces a novel approach to aspect-based sentiment analysis (ABSA) in customer reviews, leveraging the power of deep learning techniques. By addressing the inherent challenges of capturing nuanced sentiments related to specific aspects or features within textual content, our proposed model combines the strengths of deep neural networks to automatically extract and analyze sentiment-bearing features. We employ a sophisticated architecture that incorporates both word embeddings and attention mechanisms, allowing the model to discern and weigh the importance of various aspects in context. Through extensive experimentation and evaluation on diverse datasets, we demonstrate the superior performance of our deep learning-based ABSA model compared to traditional methods, showcasing its ability to provide more accurate and contextually aware sentiment analysis within the complex landscape of customer reviews. This research contributes to advancing the field of sentiment analysis by offering a robust and effective solution for extracting aspect-specific sentiments from unstructured text data